PENGELOLAAN PERGURUAN TINGGI MENGACU SATU DATA INDONESIA DALAM MEMPERKUAT PENDIDIKAN BANGSA : (TINJAUAN BERDASARKAN PERATURAN PRESIDEN (PERPRES) NO.39 TAHUN 2019) - Suprihadi, Deni; Jentot Tugiyono (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2023)
Abstract: Indonesian through Presidential Regulation (PERPRES) No. 39 of 2019, strives to implement a quality government based on data that is credible, accountable and up-to-date and becomes a reference in making policies that will be taken for government management. Implementing Presidential Decree No.39 of 2019 is not easy and tends to face quite big challenges. Satu Data Indonesia aims to unite data resources owned by various government agencies, create information transparency, and increase data interoperability. In the context of quality government administration, the implementation of PERPRES no. 39 of 2019 is the main key in ensuring that the data used by the government is accurate, consistent and can be accessed easily. The Governance of One Higher Education Data which refers to Presidential Decree number 39 of 2019 which is implemented in the tertiary environment is expected to facilitate the data synchronization process and be a solution to several problems such as university data not being the same as data in study programs, unclear university data that can accessed by both study programs and the public, in this case the community, there is no data transparency, lack of quality statistical data and preparation of higher education accreditation instruments (IAPT). Keyword: Satu Data Indonesia, Good Governance